BUDAYA AWAL HOLOSEN DI GUNUNG SEWU - Simanjuntak, Harry Truman (BRIN, 1999)
Research carried out so far, both through purely Puslit Arkenas field programs, in collaboration with France and assistance from the Toyota Foundation, has made various advances in an effort to understand the prehistory of Gunung Sewu. Various problems have been resolved and all of them are related to the process of settlement and exploitation of this area, since its existence until the approaching historical period. This paper tries to discuss specifically the culture that developed from the early Holocene to the approaching Neolithic, or what is generally called as mesolithic. The discussion will be based on the results of research in the Braholo and Song Keplek caves with some supporting data from other caves.